Kinds of materialas to use as homework (2000)
As our environment is basically monolingual, there is an absence of an adequate linguistic context, except for some music in English, cable TV or internet. In order to reinforce what students learn in English class, teachers try to assign extraclass exercises in order to complement students’ learning, but these exercises or homework must be attractive and interesting for them. It is clear that the kind of material used as homework is important to motivating students to do it.